Shifting Imaginaries amidst the apocalyptic present: African Eco-fiction and cosmologies of connection - (:unkn) unknown (My University, 2023)
The paper addresses the emergency characters of environmental imaginaries looking at cosmological issues behind them: the place humans have arrogated themselves in relation to ecosystems. The analysis starts deconstructing the Western 'cosmogony': the economic and political system that has cannibalized the entire world since 1492, culminating with the partition of Africa. African ecocritical fiction helps to envision the scale and urgency of the threat. Fictional representations of ecological realities in sub-Saharan Africa are analysed using Congo Inc. Bismarck's Testament and How Beautiful We Were as representative texts. Perspective analysis is framed by the postcolonial ecocritical postulations of Rob Nixon and Cajetan Iheka, questioning the anthropocentric view of the environment which reinforces the nature-culture divide. Contributions from different perspectives discuss the power of cosmologies and speculative imagination to envision alternative planetary futures and the fabrication of new imaginaries.
Keywords: African Research